Penguatan Kelembagaan Unit Usaha Taman Wijaya Pojok - Hery Sawiji; Subroto Rapih; Wiedy Murtini; Nur Rahmi Akbarini; Tutik Susilowati (Universitas Majalengka, 2024)
BUMDes aims to improve the village economy and increase the income of the village community through the management of natural resources, social potential, and economic potential owned by the village. Village independence can be measured by its ability to finance village government activities both in terms of government, development and society. Pojok Village is one of the villages in Mojogedang Sub-district, Karanganyar Regency, which has a BUMDes and one of its businesses is Taman Wijaya Pojok. In the process of running the business, there are several problems including institutional issues, business ideas and opportunities, and financial management issues. These problems are urgent to solve so that the service team seeks to provide training which is carried out in several stages. The aim of this activity is to provide training on institutional strengthening at Taman Wijaya Pojok. The participants in this training were 30 people including the village government, the staff of Taman Wijaya, and community members who sell in Wijaya Park. Pre tests and Post tests were conducted to determine how far the training participants understood the material to be targeted. The final results of the training showed that there was a change in participants' understanding marked by an increase in the average score obtained.